Ulam Problem for the Cosine Addition Formula in Sato Hyperfunctions. (12th February 2015) - Chung, Jaeyoung; Chung, Soon-Yeong
Abstract : We prove the Ulam problem for the cosine addition formula in the spaces of Schwartz distributions and Sato hyperfunctions with respect to bounded distributions and bounded hyperfunctions.